Commonly prescribed drugs a review - Escoto, Elmer J.T.
Drugs are routinely administered and prescribed in dentistry, from anesthesia to control pain in routine dental procedures, to analgesics and antibiotics for the management of post-op pain and infections. The MIMS and PDR are useful references in the prescription of commonly used drugs. At times it is better to prescribe medications based on weight, especially for pediatric patients, rather than the average dose. This article gives a review on the commonly used drugs in dentistry and how these drugs may be prescribed on a patient.
Keywords: Drug therapy